PENGARUH PEMAPARAN SINAR GAMMA ISOTOP COBALT-60 DOSIS 0,25–1 kGy TERHADAP DAYA ANTAGONISTIK Trichoderma harzianum PADA Fusarium oxysporum - Priyo Wahyudi; Untung Suwahyono; Harsoyo; Aris Mumpuni; Dwi Wahyuningsih (The East Java Biological Society, 2005)
Trichoderma harzianum is a well-known mycoparasitic fungus that has been used as biocontrol agent of many phytopathogenic fungi. One of the effort to improve the ability of wild strain of T. harzianum in its antagonistic activity is by exposed them in gamma ray iradiation. In this experiment wild strain of T. harzianum iradiated gamma ray of Cobalt-60 (0.25 kGy, 0.5 kGy, 0.75 kGy, and 1 kGy), then assess the effect of the iradiation on its growth, the antagonistic activity and chitinase activity toward Fusarium oxysporum. Results showed that iradiation of gamma ray 0.25–1 kGy has no effect on the growth of T. harzianum and its antagonistic activity, but it significantly influence the chitinase activity. Probably the fungi have repaired the damage of DNA caused by iradiation, so that the growth and even the enzymatic function has no longer affected.